Pembentukan Varietas Padi Sawah Dataran Tinggi Toleran Cekaman Suhu Rendah - Gunarsih, Cucu; Nafisah, Nafisah; Sitaresmi, Trias (Iptek Tanaman Pangan, 2016)
Low temperature becomes major constrain for rice production in high elevation. This condition causes losses because of grain filling problem. Sub-species of japonica have a low temperature tolerance, which is better than indica. Indica subspecies are most grown widely in Indonesia. Low temperature tolerance is an important character, because it is one of issue that needs more attention on plant breeding program. Indonesia local varieties with low temperature tolerance are Sarinah, Pulu ‘Mandoti, Pinjan and Lambau. Indonesian Center for Rice Research released a number of varieties tolerant to low temperature (for > 700 m asl) and early maturity, namely Batang Piaman, Inpari 26, Inpari 27 and Inpari 28 Kerinci. Developing irrigated rice varieties for low temperature tolerant by utilizing local varieties, introduction, crossbreeding and biotechnology provides opportunities to obtain low temperature tolerant varieties. In developing improved varieties for high elevation, it is recommended to use genetic materials with good seed vigor, moderate plant height, well exerted panicle, uniformity in flowering, and high fertility. Developing of new varieties tolerant to low temperature through conventional breeding approach requires longer time. However, conventional breeding has an important role in producing tolerant varieties, although physiological mechanism of the tolerance is not much known. Therefore, molecular genetics and biotechnology as more advanced approach are needed for supporting rice breeding program for abiotic stresses.